Eastward "glacier-like flow" of the Tibetan crust constrained from power-law rheology. (15th June 2019) - Panda, Dibyashakti; Mondal, Amit; Kundu, Bhaskar
Graphical abstract: Highlights: Geodetic observations across the Tibetan plateau indicate a ∼22 mm/yr of crustal motion with respect to stable Eurasia. Tibetan crust follows well-defined power-law with stress exponent (n) of 3.03 ± 0.1. Predicted range of viscosity of the Tibetan crust is from 1.3 × 10 23 to 5.1 × 10 22  Pa s. Abstract: We propose that topography can be used as a proxy for the eastward lateral "glacier-like flow" of the Tibetan crust in the Himalayan-Tibetan orogenic system. Geodetic observations across the Tibetan plateau indicate ∼22 mm/yr of crustal motion with respect to stable Eurasia by considering Newtonian channel flow model. Further, correlation between regional strain rate ( e ̇ ) and topographic elevation (h) is found to be statistically robust, with stress exponent (n) of 3.03 ± 0.1. Therefore, we suggest that the Tibetan crust follows well defined power-law relation that is consistent with the nonlinear deformation associated with dislocation-creep. Moreover, the predicted viscosity range of the Tibetan crust is consistent with the channel flow model proposed by previous investigators using different approaches in different time scales.